Functional characterization of KS-type dehydrin ZmDHN13 and its related conserved domains under oxidative stress - Yang Liu (Nature Portfolio, 2017)
Abstract Dehydrins belong to the group 2 family LEA (Late Embryogenesis Abundant) proteins, which are up-regulated in most plants during cold and drought stress. According to the number and order of the Y-, S- and K-segments, dehydrins are classified into five subclasses: YnSKn, YnKn, SKn, Kn and KnS. Here, the maize (Zea mays L.) KS-type dehydrin gene, ZmDHN13, was identified and later characterized. Expression profiling demonstrated that ZmDHN13 was constitutively expressed, but its expression was also altered by high osmosis, low temperature, oxidative stress and abscisic acid (ABA). Furthermore, the roles of the three conserved segments in phosphorylation, localization, binding metal ions and physiological functions were explored. ZmDHN13 was mainly localized in the nucleus, depending on phosphorylation status. Additional studies indicated that ZmDHN13 could be phosphorylated by CKII (casein kinase II), when the NLS (nuclear localization signal) segment and the S-segment were core sequences. The overexpression of ZmDHN13 enhanced transgenic tobacco tolerance to oxidative stress, and the three conserved segments exhibited a cooperative effect in response to environmental stresses in vivo.